Impulsive Buying Tendency among Emerging Adults Using Pay Later on E-Commerce Platforms - Priscilla Dewanto; Rayini Dahesihsari (International Journal of Business, Economics, and Social Development, 2025)
The rapid growth of e-commerce in Indonesia has increased the use of pay later services, which allow consumers to defer payments for online purchases. While offering convenience, this trend has contributed to a rising non-performing loan (NPL) rate, reaching 72.6% (around Rp 3.28 trillion), with emerging adults being the primary contributors. Their impulsive buying tendencies, influenced by identity exploration and instability, may lead to unplanned spending due to the ease of pay later services. This quantitative descriptive study surveyed 246 emerging adults (18-25 years old) who have used pay-later on e-commerce platforms. Participants completed the Impulsive Buying Tendency Scale (IBTS), adapted for pay later usage. Data were analysed using descriptive statistics, categorization, correlation, and comparative tests. Findings indicate that most pay later users show high impulsive buying tendencies, with affective dimension being stronger than cognitive aspect. These insights can help educate emerging adults on responsible pay later usage.